Natural balancing of flying capacitor voltages in multicell inverter under PD carrier-based PWM - Shukla, A.; Ghosh, Arindam; joshi, A. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2011)
The flying capacitor multicell inverter (FCMI) possesses natural balancing property. With the phase-shifted carrierbased scheme, natural balancing can be achieved in a straightforward manner. However, to achieve natural balancing with the harmonically optimal phase-disposition (PD) carrier-based scheme,the conventional approaches require (n-1)×(n-1) trapezoidal carrier signals for an n-level inverter, which is (n - 1) × (n - 2) times more than that in the standard PD scheme. This paper proposes two improved natural balancing strategies for FCMI under PD scheme, which use the same (n - 1) carrier signals as used in the standard PD scheme. In the first scheme, the on-line detections are performed of (i) the band in which the modulation signal is located, (ii) corresponding period number of the carrier, and (iii)rising or falling half cycle of the carrier waveform to generate the switching signals based on certain rules. In the second strategy, the output voltage level selection is first processed and the switchingsignals are then generated according to a rule based on preferential cell selection algorithm. These methods are easy to use and can be simply implemented as compared to the other available methods.Simulation and experimental results are presented for a five-level inverter to verify these proposed chemes.